RETRACTED ARTICLE: The unified theory of acceptance and use of DingTalk for educational purposes in China: an extended structural equation model - Yukun Hou; Zhonggen Yu (Humanities & Social Sciences Communications, 2023)
Abstract With educational technology growing by leaps and bounds, synchronous online learning platforms have become a prevalent practice worldwide. Although numerous studies unraveled the behavioral intention of educational technologies with statistical methodology, there is a paucity of that of DingTalk, one of China’s most popular online platforms for synchronous learning. This study aimed to extend the Unified Theory of Acceptance and Use of Technology (UTAUT) by incorporating new constructs and examining the factors that affect users’ behavioral intention and use behavior of DingTalk. The study collected 856 valid responses from China, which were analyzed using SPSS 23.0 and Amos 24.0. The findings indicated that (1) effort expectancy (EE), performance expectancy (PE), facilitating conditions (FC), self-efficacy (SE), and received feedback (RF) could significantly impact users’ attitudes toward behavior (ATB); (2) social influence (SI), FC, RF, and ATB could be significant predictors of user behavioral intention (BI); (3) FC, RF, and BI were found to have a significant effect on use behavior (UB); (4) the extended UTAUT model could explain 60.9% of the variance of users’ behavioral intention of DingTalk in China; (5) the study identified ATB and BI as joint mediators between certain variables in the model. The study presented a robust theoretical underpinning to explain the acceptance and use of educational technologies in China and provided insights into the future enhancement of E-learning platforms.